Pemodelan matematika model SIAT pada penyebaran penyakit HIV/AIDS di Sulawesi Selatan - Ibrahim, Muhammad; Irwan, Irwan; Pathuddin, Hikmawati (Teknosains, 2024)
HIV/AIDS is one of the infectious diseases that remains a major health issue in many regions, including South Sulawesi. This study discusses the Suceptible Infected AIDS Treatment (SIAT) model for HIV/AIDS in South Sulawesi. The purpose of this study was to build a model of the spread of HIV/AIDS using the SIAT model, analyze models and simulations to see the dynamics of HIV/AIDS cases in South Sulawesi. The initial step of the research was to build a SIAT model for HIV/AIDS, determine the equilibrium point and determine the basic reproductive value (R0). Next, analyze the stability of the equilibrium point and then determine the initial variable values and parameter values. Lastly do the simulation and interpretation of the simulation results. The results of the this study were obtained by the SIAT mathematical model in the from of a system of differential equations, where both disease-free and disease-endemic equilibrium points are stable. The basic reproduction number (R0) obtained is <1,which means thet the disease will disapper and will not spread to a population. The results of the analysis show that both types of equilibrium have negative eigenvalues so that it can be concluded that the disease-free and disease-endemic equilibrium points are stable.